Selective serotonin re-uptake inhibitors for the treatment of perseverative and maladaptive behaviours of people with intellectual disability - Branford, D.; Bhaumik, S.; Naik, B. (Journal of intellectual disability research, 1998)
A retrospective case‐note analysis was undertaken of 37 adults with intellectual disability who lived in Leicestershire, England. The subjects were prescribed one of two selective serotonin re‐uptake inhibitor (SSRI) antidepressants, i.e. fluoxetine or paroxetine, for perseverative and maladaptive behaviours. The SSRIs proved to be of no benefit for 15 subjects (40%) and led to a deterioration in a further nine cases (25%). However, some reduction of perseverative and maladaptive behaviours was achieved in 13 cases (35%). There was no difference in the responses to fluoxetine or paroxetine.